2007
DOI: 10.1088/0953-4075/40/7/003
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous peak in the spectrum of polarizational bremsstrahlung from relativistic electrons moving through a solid target

Abstract: The spectral-angular distribution of polarizational bremsstrahlung from relativistic electrons crossing a polycrystalline target is studied theoretically. The effect of substantial growth in the emission spectral density is predicted for photons emitted in the backward direction relative to emitting electron velocity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
26
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 20 publications
4
26
0
Order By: Relevance
“…The electron beam was transported to the target 7 which was fixed into the vacuum cham ber 6 by means of three rotating magnets 4, two pairs of magnetic quadrupole lenses 5, and a corrector 6, which made it possible to focus the electron beam on the place where the target was located with a size of up to 3 mm and with a divergence of, at most, 5 mrad. These values satisfied the PB measurement conditions in the backscattering geometry, which were limited by the dimensions of the transverse cross section of the electron beam and its divergence [7][8][9]. The trans verse size, the position in the vacuum channel, and the current of the electron beam were controlled by the proportional chamber 11 and a Faraday cylinder 12.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…The electron beam was transported to the target 7 which was fixed into the vacuum cham ber 6 by means of three rotating magnets 4, two pairs of magnetic quadrupole lenses 5, and a corrector 6, which made it possible to focus the electron beam on the place where the target was located with a size of up to 3 mm and with a divergence of, at most, 5 mrad. These values satisfied the PB measurement conditions in the backscattering geometry, which were limited by the dimensions of the transverse cross section of the electron beam and its divergence [7][8][9]. The trans verse size, the position in the vacuum channel, and the current of the electron beam were controlled by the proportional chamber 11 and a Faraday cylinder 12.…”
Section: Introductionmentioning
confidence: 91%
“…The potential advantages of the approach under discussion include precise knowledge of the spectrum of pseudophotons of the Coulomb field of fast electrons (the pseudopho tons play the role of the primary probe radiation), which is required within the framework of the energydispersion technique, and also the possibility of obtaining high spatial-measurement resolution because of the simple magnetic focusing of an electron beam on a target [4]. The authors of [9] showed that it is possible to significantly increase the energy resolu tion of measurements in the scheme of BP peak recording in the direction opposite to the velocity of radiating electrons, and the authors of [7] were the first to reliably record this effect. The authors of [8] showed that it is possible to measure the BP signal in the backscattering geometry under the condition that the poly crystal grain size is smaller than the length of BP signal photoabsorption, which emphasized that the developed method for studying polycrystals with submicron grain size is well-grounded.An important problem determin ing the possibility of the use of PB as a new method for studying the atomic structures of polycrystalline media is measurement of the PB signal generated in polycrys tals with a coherent-scattering-region size on the order of 10 nm.…”
Section: Introductionmentioning
confidence: 99%
“…Generally the value of PB peak width ∆ω is inverse proportional to Lorentz factor of an emitting electron γ, so that the energy resolution of the method under consideration increases with increasing γ. Unique possibility to increase the energy resolution in the process of polycrystal diagnostics is connected with coherent PB peaks emitted in a backward direction relative to the electron velocity [13]. It has been shown in [13], that ∆ω for such anomalous peaks is proportional to γ −2 and so these peaks are of interest for diagnostics tasks.…”
Section: Introductionmentioning
confidence: 99%
“…Unique possibility to increase the energy resolution in the process of polycrystal diagnostics is connected with coherent PB peaks emitted in a backward direction relative to the electron velocity [13]. It has been shown in [13], that ∆ω for such anomalous peaks is proportional to γ −2 and so these peaks are of interest for diagnostics tasks. It is significant that the analogous peaks occur in the process of coherent PB from relativistic electrons moving in a single crystal [14,15] (coherent part of PB in a single crystal is identical to well known parametric X-ray radiation [16,17,18] an emitting electron velocity have demonstrated that the spectral width of these peaks ranges up to about tens MeV [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation